ANALISIS PERBANDINGAN MINAT BERWIRAUSAHA DAN BEKERJA SEBAGAI KARYAWANDI MASA PANDEMI COVID-19 (Studi Kasus Mahasiswa ProdiManajemen UIN Sunan Ampel Surabaya) - Muchammad Saifuddin; Anisa Yusrin Nanda (Politeknik Bisnis Indonesia, 2021)
The Covid-19 pandemic not only affects the health sector, but also the economic sector. Many workers are threatened by the impact of the Covid-19 pandemic. Likewise with entrepreneurs, who experience losses due to social distancing that limit the space for business actors. This research was conducted with the aim of looking at the comparison between interest of entrepreneurship and working as an employee during the Covid-19 pandemic. This research uses a descriptive qualitative method. Based on the sampling technique using the purposive sampling method, then obtained 26 respondents. Data gathering techniques are conducted through interviews with sources. Data analysis using the Miles and Huberman model data analysis. Research results show that the interest of entrepreurship during the pandemic is higher than that interest of employees. Interest in entrepreneurship is superior, namely 17 respondents, while the remaining 9 respondents are interested in working as employees during the Covid-19 pandemic.